Sociological Examination of Selected Themes in Ayinla Omowura's Selected Songs - Adeleye, Adeyemo Olatunde (NIU Journal of Humanities, 2023)
Songs play important roles and are part and parcel of life in all African (Yoruba) societies. It may appear of the opinion that hardly do singers/musicians contribute anything positive towards the growth and development of the society, but the fact remains that there are no Yoruba traditions that do not communicate one important message or the other to the listener. Individual artists speak to the larger society through their songs, though their view of occurrences in the society may be different, their objectives are usually the same, either in shaping the society or to amend it.  Based on the above, this paper seeks to examine and discuss sociological themes in Àyìnlá Ọmọwúrà’s songs (a Yoruba Apala musician). Selected sociological themes in his songs will be discussed and analyzed, to highlight the didactic messages the artist was trying to pass across to the society. Materials such as journals, books, google and so on that will add value to the work will be used. The theoretical framework adopted for the study is the sociology of literature. Late Ayinla Omowura did not fold his hands and the study concludes that he was also very concerned with what is going on in the society. Through his songs, he educated and corrected the ills in the society. Keywords: Sociological examination, themes, Ayinla Omowura’s songs.